Appraising epidemiology data and antimicrobial resistance of urinary tract infections in critically ill adult patients: a 7-year retrospective study in a referral Brazilian hospital - Almeida, Vitelhe Ferreira de; Quiliici, Maria Clara Bisaio; Sabino, Sebastiana Silva; Resende, Daiane Silva; Rossi, Iara; Campos, Paola Amaral de; Ribas, Rosineide Marques; Gontijo Filho, Paulo Pinto (São Paulo Medical Journal, 2023)
BACKGROUND: Urinary tract infections (UTI) are highly preventable and have significant clinical and financial impact on the patient and the health care system. OBJECTIVE: To investigate UTIs in critically ill adult patients and the relationship of antimicrobial consumption and multidrug-resistant isolate. DESIGN AND SETTING: A cohort study performed in a Brazilian tertiary-care university hospital in the city of Uberlandia (MG), located at the Federal University of Uberlandia, southeast region of the country. METHODS: We analyzed a cohort of 363 patients with first episode of UTIs from the adult intensive care unit (ICU), from January 2012 to December 2018. The daily doses of antimicrobial administered were calculated. RESULTS: The incidence rate of UTI was 7.2/1000 patient days, with 3.5/1000 patient-days of bacteriuria, and 2.1/1000 patient-days of candiduria. Of 373 microorganisms identified, 69 (18.4%) were Gram-positive cocci, 190 (50.9%) Gram-negative bacilli, and 114 yeasts (30.7%). Escherichia coli and Candida spp. were the most common. Patients with candiduria had higher comorbidity score (Charlson Comorbidity Index ≥ 3), longer length of stay (P = 0.0066), higher mortality (P = < 0.0001) severe sepsis, septic shock, and were immunocompromised when compared with patients with bacteriuria. We observed correlation between antibiotics consumption and multidrug-resistant (MDR) microorganisms. CONCLUSION: The UTIs incidence was high and was mainly caused by Gram-negative bacteria that were resistant to common antibiotics. We observed increase in the consumption of broad-spectrum antibiotics in ICU correlating with MDR microorganisms. In general, ICU-acquired candiduria may be associated with critical illness and poor prognosis.